ASSESSMENT OF CROPPING SYSTEM PRODUCTIVITY, PROFITABILITY AND ECONOMIC EFFICIENCY OF WHEAT - M. Nawaz; S; A. Anjum; U. Ashraf; I. Khan; S. Hussain; A. Zohaib; Y. Hubiao; W. Zhiyong (Journal of Animal and Plant Sciences, 2020)
Cropping system throughout assessment exhibits importance for the crop production and cultural practices profitability. This field study was undertaken in semi-arid climate to devise suitable system. Wheat was sown in winter season while, summer crops include; cotton, maize and mungbean, which were sown under conventional tillage (CT), permanent beds (PB) and no tillage (NT) respectively. Yield and yield attributes were significantly influenced by tillage systems, highest productive tillers (m−2), grains per spike and 1000-grain weight (g) was observed in permanent beds (PB). Grain yield (tha−1) was also significantly higher (4.03 t ha−1) in PB. System productivity in terms of wheat equivalent yield (WEY) of maize-wheat (MW) under PB was higher (10.26 t ha−1) followed by mungbean-wheat in permanent bed (9.40 t ha−1) and cotton-wheat in conventional tillage (9.26 tha−1). Highest cultivation cost was observed in the cotton-wheat followed by maize-wheat under conventional tillage and least was observed in the mungbean-wheat in no tillage. Cotton-wheat (CW) gave maximum net field benefit (US$. 1606.53ha-1) in under PB followed by mungbean-wheat (MbW) (US$.1411.72ha-1). However, maximum benefit cost ratio (BCR) (3.77) was recorded in mungbean-wheat system. Moreover, the cotton-wheat in permanent bed system was the best possible option for acquiring high production and land use efficiency.
Keywords: Cropping system; wheat; net return; profitability; system productivity